Enhancing Beef Meat Emulsion: The Role of Banana Peel Albedo Powder - Kübra Unal; Nazik M. Dilek; Halime Alp; Nuran Erdem; Ali S. Babaoğlu (Polish Journal of Food and Nutrition Sciences)
This study aimed to evaluate the effects of banana peel albedo powder (BPAP) on the physicochemical and microstructural properties of beef meat emulsions. The emulsions were formulated with BPAP added at levels of 0% (control), 0.5%, 1.0%, and 1.5% of the weight of the raw beef used. Due to the formulation process, the final BPAP contents in the emulsions were 0%, 0.013%, 0.025%, and 0.038% ( w/v ), respectively. BPAP, 100 g, was found to contain 25.19 g insoluble and 6.20 g soluble dietary fiber. Among the minerals analyzed, calcium and zinc showed the highest content in BPAP. Incorporation of BPAP at a level of 1.5% of raw beef ( w/ w) to the emulsion resulted in the higher water holding capacity and the lowest cooking loss compared to control. Furthermore, the addition of BPAP up to a 1.0% of raw beef ( w/w ) level enhanced the emulsion capacity, emulsion stability, and apparent viscosity of the samples. Confocal laser scanning microscopy micrographs revealed that the emulsions containing BPAP at 0.5% and 1% of raw beef ( w/w ) exhibited a more stable and homogeneous microstructure. These findings suggest that BPAP, particularly at 1.0% of raw beef ( w/w ) level (0.025% in emulsion, w/v ), can be effectively utilized as a natural functional ingredient to improve the quality of meat emulsions in food formulations.